One Anastomosis Transit Bipartition (OATB): rational and mid-term outcomes - Ribeiro, Rui (2023)
Background: The "One-anastomosis transit bipartition" (OATB) is a promising emerging technique in the metabolic syndrome treatment. Objective: To demonstrate the results achieved with OATB in the first 5 years after surgery. Method: Cross-sectional, retrospective study, with individuals undergoing primary OATB. Individuals included in the study were: ≥ 18 years, BMI ≥ 35 kg/m2; and excluded smoking habits, drug dependence, inflammatory bowel diseases. The data analyzed demographic, anthropometric, surgical, clinical, and nutritional. Results: Sixty eight participants, 75% women, average age 45.5 years and BMI 41 kg/m2. Associated diseases: osteoarthritis (52.9%), hypertension (48.5%) and type 2 diabetes mellitus-T2DM (39.7%). All underwent laparoscopy, without conversions. Average operative time is 122.6 ± 31.7 min, and hospital stay is 2.2 ± 0.8 days. The common channel length 27 and 41 patients with 250 cm and 300 cm respectively. We registered no intraoperative complications, 2 (2.9%) early complications, and 14 (20.6%) late complications. In the first 6 months, 94.7% (250 cm) and 88.9% (300 cm) of the patients no longer used medication for T2DM, with no statistical difference between the two groups. The incidence of nutritional disorders at any time during follow-up: hypovitaminosis D (14.7%), folate hypovitaminosis (14.7%), elevated PTH (7.4%), hypoproteinemia (5.9%) and anemia (5.9%). We found no statistically significant difference between 250 and 300 cm common channel groups. Conclusion: We conclude that OATB is a safe and effective technique, demonstrating good control of T2DM and metabolic syndrome. There is a requirement to treat previous nutritional deficits. We need more long-term evidence and comparison to other surgical techniques. Keywords: Bariatric surgery; Metabolic surgery; OATB; Obesity; One-anastomosis transit bipartition; SASI; Single anastomosis sleeve-ileostomy; Transit bipartition.